Alberto Salas Plays Paka Paka con la Papa - Fajardo, Sara Andrea; Martinez-Neal, Juana (New York : Roaring Brook Press, 2025)
"What can a potato do? To Peruvian scientist Alberto Salas, they have the power to change the world. Go on the hunt with Alberto for for wild potatoes before they go extinct in this playful picture book biography, gorgeously illustrated by Caldecott-honoree Juana Martinez-Neal."-- Provided by publisher.
Keywords: Salas, Alberto, -- 1943- -- Juvenile literature; Salas, Alberto, -- 1943-; Potatoes -- Juvenile literature; Scientists -- Peru; Biography; Juvenile literature; Picture book